Controlled Atomic Solubility in Mn‐Rich Composite Material to Achieve Superior Electrochemical Performance for Li‐Ion Batteries. Issue 5 (16th December 2019) - Lee, Junghwa; Zhang, Qinghua; Kim, Jieun; Dupre, Nicolas; Avdeev, Maxim; Jeong, Mihee; Yoon, Won‐Sub; Gu, Lin; Kang, Byoungwoo
Abstract: The quest for high energy density and high power density electrode materials for lithium‐ion batteries has been intensified to meet strongly growing demand for powering electric vehicles. Conventional layered oxides such as Co‐rich LiCoO2 and Ni‐rich Li(Ni x Mn y Co z )O2 that rely on only transition metal redox reaction have been faced with growing constraints due to soaring price on cobalt. Therefore, Mn‐rich electrode materials excluding cobalt would be desirable with respect to available resources and low cost. Here, the strategy of achieving both high energy density and high power density in Mn‐rich electrode materials by controlling the solubility of atoms between phases in a composite is reported. The resulting Mn‐rich material that is composed of defective spinel phase and partially cation‐disordered layered phase can achieve the highest energy density, ≈1100 W h kg −1 with superior power capability up to 10C rate (3 A g −1 ) among other reported Mn‐rich materials. This approach provides new opportunities to design Mn‐rich electrode materials that can achieve high energy density and high power density for Li‐ion batteries. Abstract : The new strategy of achieving both high energy density and power density in Mn‐rich materials by controlling the solubility of atoms between the spinel phase and layered phase in a composite is presented. The resulting defective spinel structure and partially increased cation‐disordered layered composite structure has the highest energy density and excellent rate capability among reported Mn‐rich materials.